Regulation of The Use of Marijuana for Medical Purposes: A Comparison of Civil Law and Common Law Legal Systems - Kartika, Arie; Azwar, Tengku Keizerina Devi (Universitas Medan Area, 2024)
This study aims to determine the Regulation of the Use of Marijuana for Medical Purposes: Comparison of Civil Law and Common Law Legal Systems. This research uses normative juridical research methods using literature studies derived from Legislation, scientific journals, books related to medical cannabis discourse and analyzed qualitatively. Regulations related to Class I Narcotics in Indonesia are regulated in Law Number 35 of 2009 and Regulation of the Minister of Health of the Republic of Indonesia Number 30 of 2023. The use of cannabis as medicine is an urgent need. European countries are at the forefront of legalizing medical cannabis. Some European countries with a Civil Law legal system have different regulations in legalizing marijuana for medical purposes based on ownership restrictions. Meanwhile, countries with a Common Law legal system establish medical cannabis legalization policies based on the needs of patients, the quality of health provision, and the protection of patient rights. This study concludes that countries with a Common Law legal system have a pragmatic, case-based legal style that functions through logical reasoning while countries with a Civil Law legal system are more about practical implications.